Anatomical variations of the circle of Willis and cerebrovascular malformations on computed tomography angiography - Bertado-Ramírez, Nancy Rosalía (2025)
Objective: To determine the prevalence of anatomical variations of the circle of Willis (CoW) and their association with cerebrovascular malformations detected on cerebral computed tomography angiography (CTA). Materials and methods: A descriptive, observational, cross-sectional study was conducted at a tertiary-care hospital involving a Mexican population. Patients of all ages and both sexes, with complete medical histories and a cerebral CTA scan, were included. Patients with incomplete CTA studies or missing data were excluded. Descriptive statistics and the phi coefficient were used to assess the relationship between cerebrovascular malformations and anatomical variations of the CoW. A p value ≤ 0.05 was considered significant. All personal data were handled with strict confidentiality and used exclusively for research purposes. Results: The sample consisted of 97 patients, with a mean age of 50.19 years (range: 11–79). The cohort comprised 65 females (67 %) and 32 males (33 %). Overall, 67 patients (69 %) had at least one comorbidity and 14 (14.4 %) had multiple comorbidities. The most common indication for cerebral CTA was aneurysm detection, observed in 36 patients (37.1 %). A total of 40 patients (41.2 %) presented anatomical variations of the CoW, while 61 exhibited cerebrovascular malformations. The most prevalent vascular variation was hypoplasia, found in 25 cases (62.5 %). The correlation between anatomical variations of the CoW and cerebrovascular malformations showed a phi coefficient of -0.05 and a p value = 0.095. Conclusions: The study found a weak, statistically non-significant negative correlation between anatomical variations of the CoW and cerebrovascular malformations. The classic anatomical configuration of the CoW was observed in 59 % of cases, with the anterior communicating artery being the most frequently observed anatomical variation.